A Rhetorical Analysis of Ustadz Felix Siaw's Da'wa on Youtube - Hamdani, Syaifullah; Japeri, Japeri; Yazan, Sheiful; Fauzi, Muhammad (International Journal of Islamic Studies Higher Education, 2022)
There are many aspects that make a da'i popular among mad'u, one of which is rhetoric. Rhetoric is a style of conveying messages conveyed by da'i to mad'u. By conveying a good message, it will raise the dignity and degree of the da'i. This study aims to determine Ustadz Felix Siauw's rhetorical style including language style, voice style, and gesture style. The method used in this study uses a qualitative research method with a content analysis approach. The data collection technique is observing or watching videos that have been uploaded on the "Felix Siauw" YouTube channel. Then analyze the words that contain the application of language style, sound, and gestures. While the data source is the YouTube channel "Felix Siauw" itself and supporting knowledge such as books, journals, the internet or other references that discuss rhetorical style. From this study, the results showed that Ustadz Felix Siauw applied the rhetorical style very well in his lectures. First, the style of language used is more inclined to use words that are gentle, polite, do not provoke provocation, and create a peaceful atmosphere. On the other hand, the language used is firm and straightforward. Second, the rhythmic style of voice, found a flat tone when explaining history with moderate vocals so that it touches the listeners. Third, apart from the style of language and style of voice, Felix also uses the style of gestures such as the style of the body and eye gaze, the style of dress that is polite and neat, the style of facial expressions and hand movements. The results obtained from the research can be a reference for preachers to preach in spreading Islamic teachings.